Наші презентації (Слово і Час, 2022)
Пуніна О. Людина без шкіри. Психотип Василя Стуса; Грушевський М. С. Щоденник (1902—1914 рр.): У 2 т.; Palko O. Making Ukraine Soviet: Literature and Cultural Politics under Lenin and Stalin; Соловей О. Речник Апокаліпси (До розуміння творчої місії Олеся Ульяненка). Olha Punina. A Man without Skin. The Psychotype of Vasyl Stus; Mykhailo
Hrushevskyi. Diaries (1902—1914): In 2 vol.; Olena Palko. Making Ukraine
Soviet: Literature and Cultural Politics under Lenin and Stalin; Oleh Solovei. A
Spokesman of the Apocalypse (toward an Understanding of the Creative Mission of
Oles Ulianenko).